Utilizing Humor for Triggering Language Learners' Critical Thinking Skills: A Narrative Inquiry Study - Al Arief, Yusuf (Institut Agama Islam Negeri Palopo, 2024)
This study explores the possibility that using humor in language learning could indirectly contribute to developing critical thinking skills by promoting a positive and engaging learning environment. This study utilized a narrative inquiry approach to investigate language learners' experiences in utilizing humor to trigger students' critical thinking skills. The participants in this study were the author himself, a lecturer and 60 students of Discourse Analysis classes at the English Language Education Study Program. The data was collected through semi-structured interviews with each participant. The transcripts were read multiple times to identify recurring themes and patterns related to the use and effects of humor on the students' Critical Thinking Skills (CTS). The results showed that linguistic jokes could promote reflection and encourage language learners to think about their language use by prompting them to consider how the joke was constructed and what linguistic elements were used. There are several challenges that language teachers may face when utilizing linguistic joking to trigger students' CTS.